2014
DOI: 10.1111/iju.12396
|View full text |Cite
|
Sign up to set email alerts
|

Enigma of urethral pain syndrome: Why are there so many ascribed etiologies and therapeutic approaches?

Abstract: Urethral pain syndrome has had several sobriquets, which have led to much confusion over the existence of this pathological condition and the useful options in the care of the afflicted patient. Our aim was to explore the proposed etiologies of this syndrome, and to provide a critical analysis of each proposed etiology and present a balanced argument on the plausibility of the proposed etiology and therapeutic approaches. We carried out an English language electronic search in the following databases: Medline,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 29 publications
0
24
0
1
Order By: Relevance
“…It is not specific for women, as it can also occur in men [ 43 ], but in this case, it is customary to speak about prostatic, scrotal, or penile chronic pelvic pain [ 8 ]. A large number of studies have been devoted to the study of UPS and chronic pelvic pain in men [ 44 , 45 , 46 , 47 , 48 ], while UPS in women has been studied significantly less [ 3 , 6 ]. Therefore, one of the motivations was to conduct research on the female urethra.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not specific for women, as it can also occur in men [ 43 ], but in this case, it is customary to speak about prostatic, scrotal, or penile chronic pelvic pain [ 8 ]. A large number of studies have been devoted to the study of UPS and chronic pelvic pain in men [ 44 , 45 , 46 , 47 , 48 ], while UPS in women has been studied significantly less [ 3 , 6 ]. Therefore, one of the motivations was to conduct research on the female urethra.…”
Section: Discussionmentioning
confidence: 99%
“…The most common reason for women to seek medical attention is dysuria, and it is believed that in 40% of cases urethritis and/or urethral syndrome are involved [ 1 ]. According to the US National Institutes of Health, one third of women with chronic pelvic pain (CPP) have urethral pain syndrome (UPS) [ 2 , 3 ]. The European Association of Urology defines UPS as the occurrence of chronic or recurrent episodic pain lasting for more than 6 months, and felt in the urethra, in the absence of proven infection or other obvious local pathology.…”
Section: Introductionmentioning
confidence: 99%
“…The most common reason for women to seek medical attention is dysuria, and it is believed that in 40% of cases urethritis and / or urethral syndrome are involved [1]. According to the US National Institutes of Health, one third of women with chronic pelvic pain (CPP) have urethral pain syndrome (UPS) [2,3]. The European Association of Urology defines UPS as the occurrence of chronic or recurrent episodic pain lasting for more than 6 months, and felt in the urethra, in the absence of proven infection or other obvious local pathology.…”
Section: Introductionmentioning
confidence: 99%
“…The UK Database of Uncertainties about the Effect of Treatments (DUET) has recognized Urethral Pain Syndrome (UPS) as a knowledge gap [4]. There are few randomized controlled trials and there is no evidence-based treatment of UPS [5, 6]. The syndrome is most frequent in women but is also seen in men and children [5].…”
Section: Introductionmentioning
confidence: 99%
“…There are few randomized controlled trials and there is no evidence-based treatment of UPS [5, 6]. The syndrome is most frequent in women but is also seen in men and children [5]. UPS has a large impact on the patients’ quality of life; a study with clinical interviews showed higher levels of hostility, irritability, anxiety, dysphoria and depression among the UPS patients than in controls [7, 8].…”
Section: Introductionmentioning
confidence: 99%